Preparation of starch-based functional food nano-microcapsule delivery system and its controlled release characteristics - Tian, Shuangqi; Xue, Xing'ao; Wang, Xinwei; Chen, Zhicheng (Frontiers in Nutrition, 2022)
Most of the functional substances in food are absorbed in the small intestine, but before entering the small intestine, the strong acid and enzymes in the stomach limit the amount that can reach the small intestine. Therefore, in this paper, to develop a delivery system for functional food ingredients, maintain the biological activity of the ingredients, and deliver them to the target digestive organs, preparation of starch-based functional food nano-microcapsule delivery system and its controlled release characteristics were reviewed. Embedding unstable food active ingredients in starch-based nano-microcapsules can give the core material excellent stability and certain functional effects. Starch-based wall materials refer to a type of natural polymer material that uses starch or its derivatives to coat fat-soluble components with its hydrophobic cavities. The preparation methods of starch-based wall materials mainly include spray drying, extrusion, freeze drying, ultra-high pressure, coagulation, fluidized bed coating, molecular inclusion, chemical, and enzymic methods. The controlled release of functional food can be achieved by preparing starch-based nano-microcapsules to encapsulate the active agents. It has been reported that that compared with traditional embedding agents such as gelatin, acacia gum, and xanthan gum, starch-based functional food nano-microcapsule delivery system had many good properties, including improving antioxidant capacity, bioavailability, probiotics, and concealing bad flavors. From this review, we can learn which method should be chosen to prepare starch-based functional food nano-microcapsule delivery system and understand the mechanism of controlled release.